2022
DOI: 10.1111/1742-6723.14070
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology presentations to a tertiary unit in New South Wales during the COVID‐19 pandemic first wave: A retrospective comparison study

Abstract: Objective To compare presentation numbers, class of exposure, poison severity score (PSS) and drugs ingested by patients in a tertiary toxicology service during the first wave of the COVID‐19 pandemic to the corresponding time periods in 2018 and 2019. Methods A retrospective cohort observational study of patients admitted or consulted to the Western Sydney Toxicology Service (WSTS) from ED during February to May in 2018–2020. Patient age, sex, triage category, time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…They found substantial reductions in the numbers of presentations during the most stringent COVID‐19 restrictions (11 March 2020 – 30 June 2020), except by people with stroke‐like conditions 3 . Other Australian studies have reported increased numbers of ED presentations by people with certain conditions, including presentations to New South Wales emergency departments with self‐harm or suicidal ideation by young people, particularly adolescent girls, 4 and a relative increase in the number of presentations to a tertiary toxicology service in western Sydney despite an overall reduction in ED presentations 5 …”
mentioning
confidence: 99%
“…They found substantial reductions in the numbers of presentations during the most stringent COVID‐19 restrictions (11 March 2020 – 30 June 2020), except by people with stroke‐like conditions 3 . Other Australian studies have reported increased numbers of ED presentations by people with certain conditions, including presentations to New South Wales emergency departments with self‐harm or suicidal ideation by young people, particularly adolescent girls, 4 and a relative increase in the number of presentations to a tertiary toxicology service in western Sydney despite an overall reduction in ED presentations 5 …”
mentioning
confidence: 99%